Pengaruh Faktor Higiene Terhadap Kinerja dan Perilaku Keselamatan - Ramdhani, Irin; Suherah, Suherah; Ningrat, Andi; Erniyani, Erniyani; Raodah, Raodah (Metode : Jurnal Teknik Industri, 2025)
Performance and safety behavior are crucial in a company such as PT PLN (Persero) UP3 Parepare. Therefore, research is needed to determine the hygiene factors influencing worker performance and safety behavior in achieving company goals without work accidents. The data collection technique used in this research involves primary data in the form of a questionnaire. Questionnaires were distributed to respondents, and then processed using the help of Smart PLS 4.0. The analytical tool used is Partial Least Square (PLS), a multivariate statistical technique that compares several dependent variables. The research results show that factors that significantly influence worker performance are working conditions, supervision, and interpersonal relationships. Meanwhile, factors that do not have a significant influence on worker performance are salary, company policy, and administration and supervision. Working conditions and supervision have a significant effect on worker safety behavior. Factors that do not have a significant influence on worker safety behavior are company policies and administration, salary, and interpersonal relationships.